Comparative Study of Biotin and Hydroxyapatite on Biological Properties of Composite Coating - Hamad, Qahtan A.; Al-Hasani, Fatimah J.; Faheed, Noor K. (International Journal of Biomaterials, 2022)
The ultimate goal of using biomaterials is to improve human health by restoring the function of natural living tissues and organs in the body. The present work aims to modify the composite coating layer properties by using two different types of bioactive reinforcing materials (biotin and hydroxyapatite) particles in different percentages (5% and 10%). Coatings were applied onto commercially pure Ti, SS 316 L, and SS 304 substrates by the dip-coating method. Characterization of samples includes microstructure observation by field emission scanning electron microscopy (FE-SEM), contact angle measurement (wettability), and MTT. The results show the addition of metallic particles (bioparticles) (hydroxyapatite particles, biotin) at 5 Vol. % improved the whole properties of composite materials. Using different particles’ scale size aids to enhance the combinations in the alginate matrix producing a dual effect on composite film properties. In addition, the inclusion of metallic particles has to increase the wettability by reducing the contact angle. At the same time, MTT graphs revealed that after 3 days of exposure in MG-63 cells, 316 L SS alloys’ surface following pack adhesion became more active.